صعوبات التمويل الصغير وأثره على الفئة المستهدفة دراسة ميدانية على المستفيدين من تمويل المؤسسة الوطنية للتمويل الصغير في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت البحث إلى تحديد صعوبات التمويل الصغير التي يواجهها المستفيدين من تمويل المؤسسة الوطنية للتمويل الصغير, وأثره على الفئة المستهدفة فيما يتعلق بتحسين ظروف المعيشة, وتشجيع المبادرات الفردية وزيادة فرص العمل, اعتمد البحث على المنهج الوصفي, وتمّ اختيار عينة عشوائية شملت (200) مستفيد من تمويل المؤسسة الوطنية للتمويل الصغير, تمّ توزيع الاستبانة أداة الدراسة عليهم, وتمّ استرجاع (187) استبانة, واستبعد الباحث (9) استبانات لعدم صلاحيتها للتحليل الإحصائي, وبذلك يكون عدد الاستبيانات المتبقية والصالحة للتحليل (178) استبانة, وبنسبة استجابة بلغت (89%). توصل البحث إلى عدد من النتائج أهمها: إنّ المستفيدين من تمويل المؤسسة الوطنية للتمويل الصغير يواجهون صعوبات تمويلية عند البدء بالمشروع, حيث أنّ  فوائد القروض مرتفعة جداً, كما أنّ نسبة القرض تعتبر متدنية مقارنة بحجم القرض المطلوب, بالإضافة إلى مشكلات مستمرة في تسديد الأقساط المستحقة في مواعيدها, والإجراءات الروتينية والإدارية عند تقديم طلب القرض, والفترة الزمنية الطويلة للحصول على الموافقة لطلب القرض, وعدم كفاية فترات السداد, والتشدد في طلب الضمانات. كما أظهرت النتائج أنّ التمويل الممنوح من المؤسسة الوطنية للتمويل الصغير لم يؤدي الدور المطلوب في تحسين مستوى المعيشة, وتشجيع المبادرات الفردية, وزيادة فرص العمل. The research aimed to identify the microfinance difficulties faced by the beneficiaries of the financing of the National Microfinance Institution and its impact on the target group in terms of improving living conditions, encouraging individual initiatives and increasing employment opportunities. The research was based on the descriptive approach. A random sample of 200 beneficiaries The researcher excluded (9) questionnaires for lack of validity for the statistical analysis, thus the number of remaining questionnaires valid for analysis (178) was identified, with a response rate of (89%). . The study found a number of results, the most important of which are: The beneficiaries of the financing of the National Microfinance Institution face funding difficulties at the start of the project. The loan interest is very high, the loan ratio is low compared to the size of the loan required, Scheduling, routine and administrative procedures when submitting a loan application, the long period of time to obtain approval for a loan application, insufficient repayment periods, and tightening of the guarantee application. The results showed that the funding provided by the National Microfinance Institution did not play the required role in improving the standard of living, encouraging individual initiatives and increasing employment opportunities.